Feasibility Study of Web-Based Academic Information Systems at Bhakti Semesta Salatiga Polytechnic Using The Feasibility Method of Telos - Danis Putra Perdana; Puspa Ira Dewi Candra Wulan; Rofiq Fauzi (Institut Teknologi Dirgantara Adisutjipto, 2022)
In the process of developing information systems, there are often problems that are detrimental in terms of time and money in an organization. Bhakti Semesta Polytechnic, which is a polytechnic that was only established in 2021, needs to develop an Academic Information System after observations and interviews with the academic community have been carried out, so that development can run according to needs and does not cause losses. The feasibility test is carried out using the Telos method. This method is used to determine the feasibility of a project with several criteria, namely Technical, Economy, Legal, Operational and Schedule. The results of this study indicate the value of the feasibility factor is 8.4 with an evaluation design for developing a feasible information system (B) and the risk of developing a system is relatively low